Effective Systemic Treatment of Choroidal Metastases NSCLC With Surgery After Crizotinib: A Case Report - Liu, Shilan; Liu, Xiao; Wang, Ting; Zeng, Chunhua; Ren, Baichen; Yu, Xiaodan; Xu, Min; Li, Wenjuan; Qiao, Zhihui; You, Chuanyun; Yang, Qinghui; Chen, Mei (Frontiers in Oncology, 2022)
Choroidal metastasis as an initial presenting feature of lung cancer with EML4-ALK translocation is exceedingly rare and greatly impacts patient quality of life (QOL). There are no recommended treatments for such patients, and palliative care remains limited. It is unclear whether surgical resection of primary pulmonary lesions, systemic antitumor therapy, targeted therapy, or localized ocular therapy are effective in treating choroidal metastases in EML4-ALK rearranged oligometastatic non-small cell lung cancer (NSCLC). Here, we present the case of choroidal metastases secondary to lung cancer and EML4-ALK translocation in a 57-year-old woman who firstly underwent resection of lung lesions followed by oral administration of crizotinib without local treatment or systemic chemotherapy. Since then she had a rapid and complete response to crizotinib with 27 months of progression-free survival.